Agricultural Potential of Yellow Pumpkin (Cucurbita moschata Duch.) as a Sustainable Horticultural Commodity: A Bibliometric Review of Global Data - Asmira, Sepni; Syarif, Auzar; Azima, Fauzan; Sayuti, Kesuma (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Pumpkin is one of the agricultural commodities with potential as a functional food ingredient, supported by its nutritional value and availability. Many studies have been conducted on pumpkin, including its nutritional composition, bioactive carotenoid compounds, sustainable agricultural cultivation, waste management, and utilisation as a functional food.  However, a bibliometric analysis of the agricultural potential of pumpkin has never been conducted. This study aims to map research trends on pumpkin and its potential as an agricultural commodity in the last 25 years (2000-2025). Research data were obtained from the ScienceDirect database and visualised using VOSviewer. The data visualisation showed that pumpkin is closely related to carotenoids, its main bioactive compounds. In addition, pumpkin has been associated with grafting techniques widely used in cucurbitaceae, especially in cucumber and watermelon. The most recent research on pumpkin focuses on pumpkin analogue rice, sensory analysis, and metabolomics. By visualizing the agricultural potential of pumpkin, the trend and development over time can be clearly seen. This visualisation can serve as a reference for researchers to identify the research gap in pumpkin and its future potential. Contribution to Sustainable Development Goals (SDGs):SDG 3 (Good Health and Well-Being)SDG 12 (Responsible Consumption and Production)SDG 17 (Partnerships for the Goals)